Role of the Islamic Education teacher in the Moral Improvement of Learners - Abdul Muis; Hosaini hosaini; Eriyanto Eriyanto; Agus Readi (At-Tarbiyat, 2022)
This research is driven by a student's moral decadence, which is worrying and complex, for illustration beating students to teachers who died, brawls between students, and other lawless acts; from these problems, PAI teachers play a role in improving student morale. This study describes PAI teachers' role as educators, models and role models, and evaluators in improving students' morale. The research method used in this study is a descriptive qualitative approach because the researchers wanted to describe several phenomena related to the problems and problems that occurred. The results show 1) The role of the teacher as an educator in improving the morale of students at SMP N 02 AjungJember is to always explain moral values in everyday life through cults, giving a penalty, and 5 S cultural habits (smiles, greetings, Salim, polite, and courteous), 2) The role of PAI teachers as models and role models in improving students' morale, Always trying to offer good examples for students, so they give good feedback in everyday life, 3) The role of PAI teachers as evaluators in improving students' morale, mainly by providing a thorough evaluation, because evaluation discuss analytical aspects and further evaluations in affective and psychomotor aspects.